2013
DOI: 10.5505/abantmedj.2013.30502
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Histopathologic Diagnosis in Specimens of Hysterectomy

Abstract: Amaç: Bu çalışmada benign ön tanılarla yapılan histerektomilerin, endikasyonlar ve histopatolojik tanılar açısından değerlendirilmesi amaçlandı. Yöntem: Ocak 2011 ile Aralık 2012 yılları arasında yapılmış olan 258 histerektomi olgusu endikasyonlar ve histopatolojik tanılar açısından retrospektif olarak değerlendirildi. Bulgular: En sık histerektomi endikasyonu anormal uterin kanama idi 87 (%33,72). Daha sonra sırası ile myoma uteri 73 (%28,29) ve endometrial hiperplazi 67 (%25,96) olarak tespit edildi. Diğer k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
14
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 4 publications
(4 reference statements)
6
14
1
Order By: Relevance
“…A similar incidence is reported by Ranabhat et al 36 Similar report is also by Isaoglu U. 12 Whereas Ojeda et al reported endometrial hyperplasia at 22.3%. 37 In this study atropic endometrium was the histopatholological diagnosis in 4.8% and proliferative endometrium in 9.9% of the cases.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…A similar incidence is reported by Ranabhat et al 36 Similar report is also by Isaoglu U. 12 Whereas Ojeda et al reported endometrial hyperplasia at 22.3%. 37 In this study atropic endometrium was the histopatholological diagnosis in 4.8% and proliferative endometrium in 9.9% of the cases.…”
Section: Discussionsupporting
confidence: 77%
“…12,26 Shergill SK reported leiomyoma as the commonest indication for hysterectomy 34% followed by abnormal uterine bleeding 26%. 22 Abnormal uterine bleeding (AUB) is the second commonest indication for hysterectomy in our study 26.6%, followed by adenomyosis 11% and chronic cervicitis 9.3%, benign ovarian tumor 9.1%, CIN 3 2.3%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, hysterectomy is one of the most common surgical treatments (1). Abdominal, vaginal, and laparoscopic techniques are the surgical techniques used for hysterectomy.…”
Section: Introductionmentioning
confidence: 99%